Contemporary trends in analytical electrochemistry. Assessment and prospects - Kalvoda, Robert (Univerzita Pardubice, 1997)
The aim of this article is to give, after a brief assessment of electroanalytical methods, an outlook on their future applications not only in usual or trivial chemical analysis but mainly in biosciences having the highest priority for us and the whole nature.